Complicated vesical diverticulum calculus - Che Mohamed, Siti Kamariah; Kamarudin, Norie Azilah; Kamarulzaman, Mohd Nazli; Ghazali, Hamid (2010)
Vesical diverticula are herniations of the bladder mucosa through bladder wall musculature (detrusor muscle). The size of diverticular openings has functional implications because narrow-mouthed diverticula often empty poorly, leading to stasis of urine within diverticula which can lead to stone formation or epithelial dysplasia. A vesical diverticulum calculus is a rare entity. It is usually secondary to bladder outlet obstruction. The patient typically presents with lower urinary tract symptoms, abdominal distension, or abdominal pain. We describe a case of urethral calculi with urethral stenosis, and vesical diverticula with a large diverticulum calculus. This case illustrates the importance of an accurate radiological diagnosis for an appropriate and successful surgical management.